2016
DOI: 10.1177/2053168016652420
|View full text |Cite
|
Sign up to set email alerts
|

Say our name (and say it right)! Extending Walton et al. on the evolution of race in political science scholarship

Abstract: To explore the evolution of political-science research on race, Walton et al., have done a systematic review of more than a century of publications appearing in the discipline's oldest and most prestigious journals: Political Science Quarterly and the American Political Science Review, respectively. Walton and his colleagues uncover "dual traditions" of race scholarship: an "African American Politics" (AAP) paradigm emphasizing empowerment and Blacks' cultural distinctiveness, and a "Race Relations Politics" (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…One tradition, described as the African American politics (AAP) paradigm, was oriented toward frames of black empowerment and cultural particularity, such as Black Power ideologies; the other, the race relations politics (RRP) paradigm, focused more on comparative interracial socioeconomic dynamics. In a subsequent study, McClerking & Block (2016) confirmed their earlier findings. Adding the Journal of Politics to their study, the authors write that "the dialogues taking place in mainstream journals typically fit Walton's RRP (rather than AAP) paradigm" (McClerking & Block 2016, p. 2).…”
Section: Black Power and "The New Black Politics": Several Trends In Black Power Movement Inheritancessupporting
confidence: 76%
“…One tradition, described as the African American politics (AAP) paradigm, was oriented toward frames of black empowerment and cultural particularity, such as Black Power ideologies; the other, the race relations politics (RRP) paradigm, focused more on comparative interracial socioeconomic dynamics. In a subsequent study, McClerking & Block (2016) confirmed their earlier findings. Adding the Journal of Politics to their study, the authors write that "the dialogues taking place in mainstream journals typically fit Walton's RRP (rather than AAP) paradigm" (McClerking & Block 2016, p. 2).…”
Section: Black Power and "The New Black Politics": Several Trends In Black Power Movement Inheritancessupporting
confidence: 76%